The Role of a Network of Human Resources for Health Managers in Supporting Leadership for Health Systems Strengthening in Francophone African Countries. Issue 3 (2nd July 2016) - Fujita, Noriko; Nagai, Mari; Diouf, Ibrahima Souka Ndella; Shimizu, Takayuki; Tamura, Toyomitsu
Abstract: This article presents the Vision Tokyo 2010 Network, a unique model of peer learning and information sharing among human resources for health (HRH) managers in Francophone African countries. It describes the network's origins, achievements, and factors underlying its success. The network's origins lie in an overseas training program in Tokyo between 2010 and 2014. Participants included directors and heads of HRH management departments at federal and provincial levels across nine Francophone African countries: Benin, Burkina Faso, Burundi, the Democratic Republic of Congo, Côte d'Ivoire, Niger, Mali, Senegal, and Togo. The network itself was established in 2012 based on the common strategic vision (Vision Tokyo 2010) developed during the training program, with an objective of tackling major problems to improve the performance of human resource development systems in the health systems of participants' countries. Some of the main outcomes of the network, demonstrated during the Ebola outbreak include: improved use of human resource information systems in Senegal established as a result of peer learning within the network and technical cooperation between the Democratic Republic of Congo and Côte d'Ivoire to develop standard operational procedures and to train health workers in the management of Ebola. Having a common strategic vision and contextualized framework—African house of solidarity—as a symbol for HRH system development, strong ownership by core members, participatory processes, a positive peer learning environment, and coaching-style support by partners were key elements of success in this initiative. The biggest challenge for this network thus far has been financial sustainability. However, steps are being taken to demonstrate the cost-effectiveness of networks such as these in order to garner further support from partners to invest in networked approaches rather than siloed, country-specific programs.